Aplicação do RTQ-R na avaliação da eficiência energética de edificações multifamiliares de interesse social para as zonas bioclimáticas brasileiras - Fagundes, Renata Magalhães (2014)
Different methods of managing the housing topic in Brazil were applied over time however the housing deficit still persists and in the name of economy the same project is used in any climatic situation without worring with building aspects of thermal confort and energy efficiency. The aim of this work is to evaluate and propose changes to improve the energy efficiency levels obtained by a multi-family social housing building considering its location in the different Brazilian bioclimatic zones. For this it was used the prescriptive evaluation method of the Technical Regulations for Energy Efficiency Labelling of Residential Buildings (RTQ -R). The studied building was evaluated and obtained low efficiency levels ranging between D and E in all bioclimatic zones mainly because some prerequisites were not achieved and because of the low energy efficiency of the water heating system. The building had its efficiency level considerably improved with simple changes in the windows allied to the proposition of an efficient water heating system and the search for obtaining bonus indicating that the evaluation patterns established by RTQ -R may not be rigorous enough to produce significant changes in currently developed projects causing real improvements in energy efficiency in residential buildings of the type studied in this work. Were extremely important to the results obtained by the envelope of apartments the contact of its floor with the soil the roof and solar orientation of windows and external walls.